Bioregionalization in a data-poor situation: Mapping of Uruguayan marine benthic regions - Limongi, Pablo; Ortega, Leonardo; Horta, Sebastián; Burone, Leticia; Carranza, Alvar (Frontiers in Marine Science, 2023)
Introduction The Uruguayan Exclusive Economic Zone (U-EEZ) is still lacking a technically sound and institutionally agreed system for classifying marine benthic ecosystems. This fact, added to the growing anthropic pressure marine ecosystems face in the U-EEZ, increases the vulnerability of these ecosystems and their associated biodiversity. Despite this, there is valuable and abundant disaggregated environmental and biological information for benthic systems. Methods In this work, we used ca. 4000 records of all major Phyla of benthic invertebrates to determine discrete benthic regions for the U-EEZ. We looked at the structuring forces of bathymetry, salinity, and water masses. First, we categorized the multivariate structure according to statistical significance to test a priori categories for univariate descriptors. Then, we mapped unique combinations of categories of structuring variables, which largely determine the structure and composition of benthic communities. Operationally, the variables to be analyzed were classified, and subsequently, group (cluster) and SIMPROF analyzes were performed. Results The results suggest seven bathymetric categories, two of water masses and two of salinity, significantly structuring the benthic communities. The combination of these categories suggests nine discrete benthic marine regions for the U-EEZ, with heterogeneous structural characteristics. Our results provide an initial model of distinct benthic ecological complexes in U-EEZ. Discussion However, caution should be exerted when using this model during decision-making. For example, implementing use restrictions of benthic areas should rely on further groundtruthing, including direct seafloor observations and collections. The latter is relevant since our system is based on the analysis of accumulated historical data that may or may not represent the current condition of habitats of interest.